Kaolinite fines colloidal-suspension transport in high temperature porous subsurface aqueous environment: Implications to the geothermal sandstone and hot sedimentary aquifer reservoirs permeability. (January 2021) - Kanimozhi, B.; Rajkumar, P.; Kumar, R.S.; Mahalingam, S.; Thamizhmani, Vivek; Selvakumar, Arun; Ravikumar, S.; Kesavakumar, R.; Pranesh, Venkat
Highlights: Fines migration in the hot sedimentary aquifer was investigated. Fines intrusion in porous rocks resulted in a water production decrease. Permeability decline and pressure stabilization were recorded. Abstract: Phyllosilicates, specifically, the kaolinite clay mineral (Al2 Si2 O5 (OH)4 ), which is a layered silicate mineral with one silica tetrahedral sheet connected with oxygen atoms to one alumina octahedral octahedral sheet is ubiquitous and abundant in sedimentary basins, especially sandstone formations. This particular type of clay mineral fine particles can easily and rapidly cause reservoir formation damage in high temperature aquifers, geothermal, and petroleum reservoirs by detaching from the porous rock surface and migrate, and plug the pore-throats of the rock matrix. Several factors such as, reservoir temperature, pressure, geochemical alteration, permeating fluid, reactive flow, and multi-phase flow are attributed to the permeability decline of the porous rocks and subsequent fluid flow reduction, and consequently, leading to well productivity loss. Therefore, this paper presents laboratory modeling of fines transport in the hot porous sedimentary aquifer. This type of aquifer is located in sedimentary basins with the elevated heat flow and having a characteristic of a shallow depth and a high volume, which indicates a high natural porosity and permeability. In this work, we have conducted three sets of coreflood experiments in the temperature ranges of 125 °C 150 °C, and 175 °C. Kaolinite suspension water has been injected into the porous sandstone core at these temperatures to investigate the feasibility of a permeability and injectivity decline. The major experimental results revealed that there is an increase in water saturation and heat transfer rates. The concentration of fines surges with increasing PVI and permeability declines with increased time. Pressure soars with increasing Pore Volume Injection (PVI), but it stabilized after some time. Actually, PVI is a ratio of cumulative water injection to each pore chamber volume of the rock core. Importantly, the water discharge rate decreases with increasing suspension injection and on the other side, with fresh water injection, the rate of water discharge rises steadily. Furthermore, the experimental and mathematical models were tested against statistical model, multiple linear regression for validation. The modelling results showed good agreement and, therefore, this paper has explicated the significance of fines transport in aquifers under hot sedimentary basins.